Synergistic action of earthworms and arbuscular mycorrhizal fungi associated with upland rice drives arsenic immobilization in the hyphosphere - Zipeng Chen; Yiming Cao; Yanjie Chen; Rongliang Qiu; Xu Yang; Huashou Li (Applied Soil Ecology, 2026)

Anemoside B4 upregulates DDAH2 and attenuates oxidative stress induced endothelial dysfunction - Shuxian Lu; Yao Yi; Qin Chen; Luling He; Margaret Baldini; Dan Shan; Limin Gong; Liang Qiu; Shumin Ma; Manman Qin; Yanyun Fang; Yifeng Zhang; et al. (Molecular and Cellular Biochemistry, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.